2015
DOI: 10.1016/j.fuproc.2014.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Defluidization and agglomeration of a fluidized bed reactor during Cynara cardunculus L. gasification using sepiolite as a bed material

Abstract: This work studies the defluidization time and the agglomerates generation in a Bubbling Fluidized Bed (BFB) reactor during Cynara Cardunculus L. gasification using, separately, two different bed materials, silica sand and sepiolite (Mg 8 Si 12 O 30 (OH) 4 (OH 2 ) 4 8H 2 ). The high adsorption capacity and the elemental composition of the sepiolite make it suitable as an alternative bed material in order to reduce agglomeration. Experiments were performed on a stainless steel lab-scale BFB reactor operating wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…In the present study this value was 11.38 % (dry basis) including added kaolin which had been mixed with the C. cardunculus L (Table 1) to prevent agglomeration. Previous gasification studies had reported some agglomeration problems when gasifying this energy crop due to the high amounts of alkali metals such as K and Na [23][24][25][26]. The amount of kaolin added was 3 wt.% of the biomass loaded into the feeding system.…”
Section: Biomass and Bed Materials Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study this value was 11.38 % (dry basis) including added kaolin which had been mixed with the C. cardunculus L (Table 1) to prevent agglomeration. Previous gasification studies had reported some agglomeration problems when gasifying this energy crop due to the high amounts of alkali metals such as K and Na [23][24][25][26]. The amount of kaolin added was 3 wt.% of the biomass loaded into the feeding system.…”
Section: Biomass and Bed Materials Characterizationmentioning
confidence: 99%
“…The agglomerates were found to be formed by a melted phase rich in sodium, potassium, calcium, magnesium and silicon. Serrano et al [26] used silica sand and an alternative bed material, sepiolite, in order to compare the defluidization time and agglomerates during cardoon gasification at different air velocities and observed that the sepiolite delayed the defluidization time by up to an order of magnitude compared with silica sand. These studies show that the use of different bed materials such as magnesite, olivine or sepiolite can delay agglomeration and suggest that dolomite can be used to completely avoid it.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, a previous work of Serrano et al [30] showed different agglomeration and defluidization processes for Cynara cardunculus L. gasification. On the one hand, jetsam behavior of fuel particles was found in a bed formed by sepiolite particles.…”
Section: Introductionmentioning
confidence: 72%
“…Similar results were obtained for the rest of fluidization velocities. Finally, the defluidization time for all the tests is compared to previous results reported by [30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation